2003
DOI: 10.1007/bf02348428
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory variations in the reflection mode photoplethysmographic signal. Relationships to peripheral venous pressure

Abstract: Photoplethysmography (PPG) is a non-invasive optical way of measuring variations in blood volume and perfusion in the tissue, used in pulse oximetry for instance. Respiratory-induced intensity variations (RIIVs) in the PPG signal exist, but the physiological background is not fully understood. Respiration causes variations in the blood volume in the peripheral vascular bed. It was hypothesised that the filling of peripheral veins is one of the important factors involved. In 16 healthy subjects, the respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…The HF band of PPGV represents the respiratory fluctuation in peripheral blood volume, secondary to the modulation of venous return and stroke volume by intrathoracic pressure change [5,6,11,18,26]. The LF band generally represents peripheral vasomotor activities, including those mediated by sympathetic control mechanisms [5,10,11,13,16,17,20,22,26].…”
Section: Frequency Spectrum Analysismentioning
confidence: 99%
“…The HF band of PPGV represents the respiratory fluctuation in peripheral blood volume, secondary to the modulation of venous return and stroke volume by intrathoracic pressure change [5,6,11,18,26]. The LF band generally represents peripheral vasomotor activities, including those mediated by sympathetic control mechanisms [5,10,11,13,16,17,20,22,26].…”
Section: Frequency Spectrum Analysismentioning
confidence: 99%
“…Although venous blood has generally been thought to be a static absorber of light, it has been shown that the venous blood volume does not in fact remain constant [Nilsson et al 2003]. In fact, the volume of the veins fluctuates in response to various physiological and physical effects, such as respiration [Phillips et al 2012].…”
Section: Introductionmentioning
confidence: 99%
“…1,6 Venous capacity corresponds with venous return that affects blood capacity of the heart in each contraction. If venous tone in consistent in the venous return curve, venous return decreases with the increase in central venous pressure and decreases stroke volume.…”
Section: Discussionmentioning
confidence: 99%
“…dc has many physiological meanings and correlates with the ac waveform. [1][2][3][4][5][6][7][8] According to the Lambert-Beer (or Beer-Lambert) law that explains mechanisms of PPG, PPG ac is generated by the optical path length ( d) that changes with the increase of volume in blood vessels as they pulsate. 9 Therefore, it can be said that PPG ac is in a consistent relationship generated by variations in dc and d.…”
Section: Introductionmentioning
confidence: 99%